2019
DOI: 10.1016/j.molimm.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor p53 inhibits porcine epidemic diarrhea virus infection via interferon-mediated antiviral immunity

Abstract: A B S T R A C T p53 is a tumor suppressor gene that can be activated in many contexts, such as DNA damage or stressful conditions. p53 has also been shown to be important for responses to certain viral infections. Porcine epidemic diarrhea virus (PEDV) is a major enteric pathogen of the coronavirus family that causes extensive mortality among piglets. The involvement of p53 during PEDV infection has not previously been investigated. In this study, we detected p53 upregulation in response to PEDV infection. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…P53 transactivates interferon regulatory factor 7 (IRF7) to regulate the expression of IFNα and IFNβ. Overexpression of P53 in porcine epidemic diarrhea virus (PEDV) infection, a pathogen from the coronavirus family, negatively regulates viral replication [ 137 ]. Other studies suggested that papain-like proteases (PLPs) may serve as a potential therapeutic target for viral infections [ [138] , [139] , [140] ].…”
Section: Copdmentioning
confidence: 99%
“…P53 transactivates interferon regulatory factor 7 (IRF7) to regulate the expression of IFNα and IFNβ. Overexpression of P53 in porcine epidemic diarrhea virus (PEDV) infection, a pathogen from the coronavirus family, negatively regulates viral replication [ 137 ]. Other studies suggested that papain-like proteases (PLPs) may serve as a potential therapeutic target for viral infections [ [138] , [139] , [140] ].…”
Section: Copdmentioning
confidence: 99%
“…SARS-CoV promotes the expression of a truncated form of p53 that inhibits apoptosis mediated by wild-type p53 (Leong et al, 2005). This is supported by the observation that the Porcine epidemic diarrhea virus (PEDV) production is increased in p53 knockout cells (Hao et al, 2019).…”
Section: Cell Cycle Pathwaysmentioning
confidence: 87%
“…Little is known about the role of p53 in the regulation of ACE2. An earlier study reported that p53 suppresses the replication of coronavirus through ACE2 degradation in humans [ 23 ] and inhibits the interferon-mediated antiviral immunity in pigs [ 24 ]. In this study, we show that the absence of the p53 binding site increases the activity of ACE2 promoter in porcine kidney cells.…”
Section: Discussionmentioning
confidence: 99%